Poultry husbandry, water, sanitation, and hygiene practices, and child anthropometry in rural Burkina Faso. Issue 4 (29th April 2019) - Gelli, Aulo; Headey, Derek; Becquey, Elodie; Ganaba, Rasmane; Huybregts, Lieven; Pedehombga, Abdoulaye; Santacroce, Marco; Verhoef, Hans
Abstract: Poultry production in low income countries provides households with nutrient‐rich meat and egg products, as well as cash income. However, traditional production systems present potential health and nutrition risks because poultry scavenging around household compounds may increase children's exposure to livestock‐related pathogens. Data from a cross‐sectional survey were analysed to examine associations between poultry, water, sanitation, and hygiene practices, and anthropometric indicators in children (6–59 months; n = 3, 230) in Burkina Faso. Multilevel regression was used to account for the hierarchical nature of the data. The prevalence of stunting and wasting in children 6–24 months was 19% and 17%, respectively, compared with a prevalence of 26% and 6%, respectively, in children 25–60 months. Over 90% of households owned poultry, and chicken faeces were visible in 70% of compounds. Caregivers reported that 3% of children consumed eggs during a 24‐hr recall. The presence of poultry faeces was associated with poultry flock size, poultry‐husbandry and household hygiene practices. Having an improved water source and a child visibly clean was associated with higher height‐for‐age z scores (HAZ). The presence of chicken faeces was associated with lower weight‐for‐height z scores, and no associations were found with HAZ. Low levels of poultry flock size and poultry consumption in Burkina Faso suggest there is scope to expand production and improve diets in children, including increasing chicken and egg consumption. However, to minimize potential child health risks associated with expanding informal poultry production, research is required to understand the mechanisms through which cohabitation with poultry adversely affects child health and design interventions to minimize these risks.